Optimalisasi Peranpetugas Aviation Security dalam Menja min Keamanan dan Keselamatan Penerbangan di Bandar Udara Sultan Muhammad Salahuddin Bima - Anida Awaliyah; Hodi Hodi (Student Scientific Creativity Journal, 2024)
In maintaining airport security, each airport has a security officer, namely Aviation Security (AVSEC). AVSEC are airport security personnel who are required to have responsibility for ensuring flight security who are required to have a license, the role of Aviation Security (AVSEC) officers is very important in security and safety. This study aims to determine whether the role of Aviation Security (AVSEC) officers in carrying out their responsibilities for security is in accordance with the SOP, and what problems occur when Aviation Security (AVSEC) officers are carrying out their duties. This study uses qualitative methods, data collection techniques in this study are interviews, observation, and documentation. Data analysis techniques using data reduction, data presentation, and data conclusions/verification. The results of this study indicate that the role of Aviation Security (AVSEC) officers has carried out their duties properly in accordance with applicable SOPs and always prioritizes 3S + 1C for passenger comfort. Obstacles during passenger inspection caused an error in the engine so that the inspection was not optimal and inspection of passenger luggage was carried out manually by Aviation Security (AVSEC) officers. ,